Manobra de valsalva relacionada ao volume da orelha média - Sales, Renata (2005)
Eustachian tube dysfunction (T.A.) is one of the main factors responsible for otitis media, which is a significant public health problem. To assess the functioning of the T.A., the Valsalva Maneuver (M.V.) and the clinical tympanometry test can be performed. With technological advancement, video-fibro-otoscopy appeared, which is capable of filming structures inside the ear, such as the movement of the eardrum. This study aimed to compare the visual perception of M.T. obtained during M.V., by video-fibro-otoscopy, with the middle ear volume recorded on tympanometry. The work was carried out at the Audicom S / S clinic, in the city of Ribeirão Preto - SP, involving 10 individuals (20 ears), of both sexes, in the age group of 20 to 40 years. The selected individuals were submitted to audiometry, immittance testing and video-fibro-otoscopy during M.V., with image recording. The 20 recorded images of ears were presented at random with the repetition of once each, totaling 40 images of ears on a CD. 16 judges were selected to analyze the images using the Visual analogue scale (V.A.S.) method, of which 06 individuals were speech therapists and 10 had higher education in other areas. According to the results obtained in the research, it was observed that video-fibro-otoscopy is a valid method for analyzing the movement of M.T. The judgment of the perception of the movement of M.T was different between the groups of speech therapist and non-speech therapist judges, and this judgment was statistically consistent in the first group mentioned. It is concluded that the video-fibro-otoscopy can help in the speech therapy therapies of tubal dysfunction, because it is able to show with confidence the M.T. in the different pressures inserted in the middle ear (O.M.). Tympanometry remains an important method for ascertaining the volume of O.M. and its results can be improved with the introduction of this new M.T.